The remedy for love [compact disc, unabridged] : a novel - Roorbach, Bill (Highbridge Co., 2014)
They're calling it the Storm of the Century, so Eric stops at the market for provisions. But when the unkempt young woman in line is short on cash, charity takes hold of him: twenty bucks and a ride home. She's squatting in a cabin in the woods with no electricity or heat, and just the nearby river to sustain her. She clearly doesn't realize the trouble she's in. But neither does Eric. As the snow keeps mounting and drifting, they're forced to ride out the storm together, for better or worse.